IMPACT OF THE USE OF AGRICULTURAL TOOLS AND MACHINERY ON WOMEN'S PARTICIPATION IN RICE BUSINESS IN MINASA TE'NE DISTRICT, PANGKEP REGENCY - Ekasari, Kartika; Mufidah Muis, Mufidah; Darhyati, Andi Tenri; Saade, Aminuddin; Beddu, Hartina (International Journal of Artificial Intelligence Research, 2023)
This study aims to determine the impact of using agricultural tools and machinery on women's participation in rice farming in Minasa Te'ne District, Pangkep Regency. Respondents in this study were selected directly (purposive sampling) with certain considerations. In this study, the data collected came from interviews with 153 respondents. Respondents are female farmers (Wanita Tani) who cultivate rice. The data collected in this study include primary data and secondary data. Primary data is data obtained through in-depth interviews using a tool in the form of a list of questions or questionnaires in addition to direct observation. Secondary data supports this research obtained from the results of a literature review, reports from various agencies, including the Agriculture Service, Agricultural Extension Center, District Office, Village Office, or other agencies relevant to the research. Obtained were tabulated and processed descriptively, qualitatively and quantitatively. The results showed that women's participation acted as housewives and directly contributed working time to rice farming. Efficiency has been achieved through agricultural mechanization; the revenue obtained is 1.1 times the total costs incurred. Before mechanization, women received wages of Rp. 3,071,548.31, while after mechanization, women received wages of Rp. 1,212,313.22. The difference in wages between before mechanization and after Mechanization is IDR 1,859,235.09.